A segregated spectral finite element method for the 2D transient incompressible Navier–Stokes equations. (15th January 2020) - He, Wenqiang; Qin, Guoliang; Lin, Jingxiang; Jia, Cheng
Abstract: In this paper, the spectral element approximation and the velocity–pressuredecoupling method implementing the SIMPLE (semi-implicit method for pressure linked equations) algorithm are first combined to form a high-order segregated scheme for the solution of the two-dimensional transient incompressible Navier–Stokes equations. In contrast to previous segregated finite element methods based on the SIMPLE algorithm, the pressure equation is derived from the continuity equation using the element matrices to ensure convergence. High-order element basis functions are adopted, which greatly reduces the number of nodal points used in the calculation. The validation test that has an analytical solution demonstrates the high accuracy and convergence rate of the method. The flow in a lid-driven cavity with different inclination angles and the flow over a backward-facing step are investigated to further illustrate the performance of the scheme. The computed results are in excellent agreement with the benchmark solutions. The almost periodic solution for the flow of Re =10000 in a lid-driven square cavity is also captured by the present scheme.